Functional Task Constraints Foster Enhanced Postural Control in Children With Cerebral Palsy. Issue 3 (1st March 2016) - Schmit, Jennifer M.; Riley, Michael; Cummins-Sebree, Sarah; Schmitt, Laura; Shockley, Kevin
Abstract : Background: Postural instability is a classical characteristic of cerebral palsy (CP), but it has not been examined during functional play activity. Recent work has demonstrated that when motor tasks are made functionally more relevant, performance improves, even in children with movement pathology. It is possible that in a disease state, the underlying control mechanisms that are associated with healthy physiology must be elicited. Objective: The study objective was to explore the utility of the functional play task methodology as a more rich and interpretable approach to the quantification of postural instability in children with CP. Design: Postural stability measures obtained from a cross-sectional cohort of children with CP (n=30) were compared with stability measures taken from children with typical development (n=30) during a single measurement period. Methods: Postural stability data were obtained with a portable force platform system. Postural sway was quantified during a precision manual functional play task. A baseline condition (no task) also was included. Postural sway variability and postural sway regularity were analyzed with analyses of variance. Results: There was an apparent difference in postural control (greater irregularity, greater sway variability) during quiet stance between children with CP and peers with typical development; this difference was mitigated during the performance of the precision functional play task. Limitations: A small and nonprobability sample of convenience may limit the findings of this study. Conclusions: The findings illustrate flexibility and adaptability in the postural control system despite the pathological features associated with CP.